(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
The implementation of Hospital Management Information Systems aims to deliver precise and current information to support management and decision-making processes in hospitals. Although many hospitals have adopted SIMRS, challenges related to data management and operational efficiency are still prevalent. Using a literature review methodology, this paper examines 10 scientific articles published between 2020 and 2024. The analysis results indicate that the success of SIMRS implementation is affected by a number of things, such as service quality, organizational structure, user satisfaction, and technological support. Key findings include the significant impact of system complexity and motivation on nurses’ behavior, as well as the importance of human resources, training, and managerial support. Additionally, a conducive work culture and the appropriate selection of technology also contribute to the success of SIMRS. This study is expected to serve as a reference for improving understanding and expertise in managing hospital management information systems.